2020
DOI: 10.1016/j.ejvs.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Landing Zone Remodelling after Endovascular Repair of Dissected Descending Aorta

Abstract: WHAT THIS PAPER ADDSThe distal landing zone in patients undergoing endovascular repair for descending aortic dissection is frequently dissected. In this report it is shown that in a substantial number of patients stent grafts attain their nominal diameter at follow up and the dissected landing zone diameter continues to increase. The risk of distal stent graft induced new entries and the aortic diameter's increase at the distal landing zone make the subsequent follow up imaging monitoring in these patients man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…However, TEVAR with standard thoracic platforms in the setting of CTBAD carries a significant risk of dSINE, 6 which in turn may lead to aneurysm expansion, and warrant re-intervention. [7][8][9][10] Furthermore, dSINE have been lately recognized as a potential complication also following deployment of FET devices in patients undergoing proximal repair for type A dissection 11 , 12 (as noted in 2 patients from the present series).…”
Section: Discussionmentioning
confidence: 64%
“…However, TEVAR with standard thoracic platforms in the setting of CTBAD carries a significant risk of dSINE, 6 which in turn may lead to aneurysm expansion, and warrant re-intervention. [7][8][9][10] Furthermore, dSINE have been lately recognized as a potential complication also following deployment of FET devices in patients undergoing proximal repair for type A dissection 11 , 12 (as noted in 2 patients from the present series).…”
Section: Discussionmentioning
confidence: 64%
“…It could only be shown that excessive oversizing with respect to the true lumen diameter at the distal landing zone can lead to dSine and increased risk of aneurysm formation with subsequent rupture. Since 80% of the cases are treated with a distal landing zone of TEVAR in the dissected aorta [24], the use of tapered stent grafts to avoid excessive oversizing is recommended [6][7][8][9]25].…”
Section: Discussionmentioning
confidence: 99%
“…Endoleak was an independent risk factor for early death and was the main cause of death after TEVAR during the long‐term follow‐up 16–18 . Berkarda et al found that the distal landing zone was dissected in 84% of the patients, and the diameter of the dissected distal landing zones measured for the true lumen and the entire aorta had increased by 7 and 4 mm, respectively, 1 year after TEVAR 19 . The long‐term mortality was also remarkably high in our series, and 5 of the 21 patients died suddenly during the follow‐up period.…”
Section: Discussionmentioning
confidence: 99%